2011
DOI: 10.1038/nature09754
|View full text |Cite
|
Sign up to set email alerts
|

MHC class II transactivator CIITA is a recurrent gene fusion partner in lymphoid cancers

Abstract: Chromosomal translocations are critically involved in the molecular pathogenesis of B-cell lymphomas, and highly recurrent and specific rearrangements have defined distinct molecular subtypes linked to unique clinicopathological features1,2. In contrast, several well-characterized lymphoma entities still lack disease-defining translocation events. To identify novel fusion transcripts resulting from translocations, we investigated two Hodgkin lymphoma cell lines by whole-transcriptome paired-end sequencing (RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
405
1
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 550 publications
(422 citation statements)
references
References 41 publications
2
405
1
4
Order By: Relevance
“…[56][57][58] Most of them have discovered a considerable fraction of fusion transcripts -that is chimeric mRNAs that may alter cell's functionality -commonly produced by genomes rearrangement and critically involved in the pathogenesis of several types of malignancies. However, it should be noted that some of the newly identified rearrangements may not be the molecular cause of the aberrant phenotypes, and that using RNA-Seq solely allows detecting expressed fusion genes giving no information about other kind of structural rearrangements.…”
Section: Rna-seq In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…[56][57][58] Most of them have discovered a considerable fraction of fusion transcripts -that is chimeric mRNAs that may alter cell's functionality -commonly produced by genomes rearrangement and critically involved in the pathogenesis of several types of malignancies. However, it should be noted that some of the newly identified rearrangements may not be the molecular cause of the aberrant phenotypes, and that using RNA-Seq solely allows detecting expressed fusion genes giving no information about other kind of structural rearrangements.…”
Section: Rna-seq In Cancermentioning
confidence: 99%
“…In a recent study on B-cell lymphomas, MHC class II transactivator (CIITA) has been identified as a novel partner of various fusions transcripts, suggesting a possible novel intriguing genetic mechanism underlying the onset of lymphoid cancers. 58 Moreover, the application of RNA-Seq to breast cancer samples has allowed to detect alternative splicing events associated with epithelialmesenchymal transition (EMT), suggesting the classification of cancer cell lines into basal and luminal subtypes, based on their EMT-associated splicing pattern. 62 Furthermore, the integration of multiple levels of analysis has allowed the identification of fusion genes associated with CNVs, suggesting that fusion events may contribute to the selective advantage provided by DNA amplifications and deletions, or may mediate the activation of a dormant gene.…”
Section: Rna-seq In Cancermentioning
confidence: 99%
“…46,47 These structural alterations appear to occur at a low frequency, although this might be underestimated due to the heterogeneity of clinical samples. Mutations in the HLA class II-regulatory gene RFX5 were found at frequency of about 30% of HLA class II antigen-negative microsatellite-unstable (MSI-H) CRC (28.9%), while CIITA mutations were only found in about 5% of these lesions.…”
Section: Structural Alterations Of Hla Class II Apm Components In Malmentioning
confidence: 99%
“…30 However, MHC II is shown to be downregulated in a subset of classical Hodgkin lymphoma cases, 32 partly owing to translocations involving the MHC II transactivator (CIITA). 33 Decreased MHC class II expression has been linked to reduced tumor cell immunogenicity. A strong expression of STAT3 was observed in Hodgkin and Reed-Sternberg cells in the present and previous studies.…”
Section: Discussionmentioning
confidence: 99%